Sirtuin 6 inhibits group 3 innate lymphoid cell function and gut immunity by suppressing IL-22 production - Su, Xiaohui; Zhao, Linfeng; Zhang, Huasheng; Wang, Dongdi; Sun, Jiping; Shen, Lei (Frontiers in Immunology, 2024)
Group 3 innate lymphoid cells (ILC3s) express the transcription factor RORt and produce cytokines IL-22 and IL-17. They are enriched in the intestinal mucosa and play important roles in host defense against infection and inflammatory diseases. Sirtuin 6 (SIRT6) is a nicotinamide adenine dinucleotide (NAD + )-dependent deacetylase and has been shown to control intestinal epithelial cell differentiation and survival. However, the role of SIRT6 in ILC3s remains unknown. Here, we show that SIRT6 inhibits IL-22 expression in intestinal ILC3s in a cell-intrinsic manner. Deletion of SIRT6 in ILC3s does not affect the cell numbers of total ILC3s and subsets, but results in increased IL-22 production. Furthermore, ablation of SIRT6 in ILC3s protects mice against Citrobacter rodentium infection and dextran sodium sulfate-induced colitis. Our results suggest that SIRT6 may play a role in ILC3 function by regulating gut immune responses against bacterial infection and inflammation.